Solid waste silicon-aluminum-based alpha-iron oxide ceramic membrane as well as preparation method and application thereof
By using silicon-aluminum-based α-iron oxide ceramic film made of solid waste and coated with α-Fe2O3 sol on its surface, the problem of cumbersome and high cost of handling oil-containing emulsion wastewater in the prior art is solved, and efficient and low-cost wastewater treatment effect is achieved.
Patent Information
- Application Number
- CN202510009990.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-03
- Publication Date
- 2025-04-11
- Estimated Expiration
- 2045-01-03
AI Technical Summary
The prior art is cumbersome, expensive and difficult to produce and apply on a large scale when treating oil-containing emulsion wastewater.
A solid waste silicon-aluminum-based α-iron oxide ceramic film is used. The film is made of solid waste such as gold ore tailings, electroplating sludge, bran, aluminum trioxide and silica, and is coated with α-Fe2O3 sol on the surface and prepared by a low-temperature sintering process.
It realizes efficient treatment of high-concentration oil-containing emulsion wastewater, reduces production costs and energy consumption, and improves the oil repellency of the ceramic membrane through the load of α-Fe2O3.
Smart Images

Figure CN119797962A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of sewage purification and waste resource utilization, and in particular relates to a solid waste silicon-aluminum-based alpha-iron oxide ceramic membrane and a preparation method and application thereof. Background Art
[0002] In the production industries such as chemical pharmaceuticals, metal smelting, and food processing, oily wastewater is generated during equipment cleaning and machine lubrication. Oily wastewater entering the water source will cause the death of organisms, and entering the soil will greatly affect the soil ecology. Conventional treatment methods mainly include gravity separation, centrifugal separation, flocculation sedimentation, coarse granulation method, and flotation method, all of which use different water treatment equipment to remove or reduce the content of harmful substances in oily wastewater.
[0003] Membrane separation technology is considered to be the water treatment technology of the 21st century. It is a general term for a large category of technologies. It mainly includes microfiltration, ultrafiltration, nanofiltration and reverse osmosis. These membrane separation products all use the interception ability of specially manufactured porous materials to remove impurities of a certain particle size in the water by physical interception. Among membrane separation products, inorganic ceramic membranes have the advantages of high temperature resistance, high mechanical strength, excellent impact resistance, chemical corrosion resistance, long life cycle, and environmental friendliness. They are ideal water treatment materials. At present, the main components of commercial inorganic ceramic membranes include zirconium oxide, aluminum oxide, silicon dioxide, titanium dioxide and silicon carbide. Due to the scarcity of drugs in the preparation process and the complexity of the sintering process, the market share of commercial ceramics is not high. Therefore, how to prepare low-cost and efficient ceramic membranes is extremely important. Summary of the invention
[0004] In order to solve the above technical problems, the present invention proposes a solid waste silicon-aluminum-based α-iron oxide ceramic membrane and its preparation method and application, so as to solve the problems of the above-mentioned prior art in the treatment of oil-containing emulsion wastewater, such as complicated operation, high cost and difficulty in large-scale production and application.
[0005] To achieve the above object, the present invention provides the following technical solutions:
[0006] One of the technical solutions of the present invention:
[0007] A solid waste silicon-aluminum-based α-iron oxide ceramic membrane (solid waste silicon-aluminum-based α-Fe2O3 ceramic membrane), comprising a solid waste silicon-aluminum-based ceramic membrane and an α-Fe2O3 sol coated on one side of the solid waste silicon-aluminum-based ceramic membrane;
[0008] The coating amount of the α-Fe2O3 sol on the surface of the solid waste silicon-aluminum-based ceramic membrane is 0.1-0.3 mL·cm -2 , preferably 0.15 mL·cm -2 ;
[0009] The solid waste silicon-aluminum-based ceramic membrane raw materials include gold mine tailings, electroplating sludge, bran, aluminum oxide and silicon dioxide.
[0010] Furthermore, the mass ratio of the gold mine tailings to the electroplating sludge is (0-3): (3-0), wherein the amount of the gold mine tailings and the electroplating sludge is not 0;
[0011] The bran accounts for 2% of the total mass of the solid waste silicon-aluminum-based ceramic membrane raw materials;
[0012] The aluminum oxide accounts for 9% of the total mass of the solid waste silicon-aluminum-based ceramic membrane raw materials;
[0013] The silicon dioxide accounts for 4% of the total mass of the solid waste silicon-aluminum-based ceramic membrane raw materials.
[0014] The second technical solution of the present invention:
[0015] A method for preparing the solid waste silicon-aluminum-based α-iron oxide ceramic membrane comprises coating α-Fe2O3 sol on one side of the solid waste silicon-aluminum-based ceramic membrane, drying and calcining to obtain the solid waste silicon-aluminum-based α-iron oxide ceramic membrane.
[0016] Furthermore, the drying temperature is 60-80° C. and the drying time is 6-12 hours.
[0017] Furthermore, the calcination is carried out by heating the material to 500° C. at a heating rate of 5° C. / min in an air atmosphere, keeping the temperature for 120 minutes, and then cooling the material to room temperature.
[0018] Furthermore, the method for preparing the solid waste silicon-aluminum-based ceramic membrane comprises the following steps:
[0019] Gold mine tailings, electroplating sludge, bran, aluminum oxide and silicon dioxide raw materials are crushed and then mixed and ball-milled to obtain ceramic membrane powder, and the ceramic membrane powder is pressed and calcined to obtain the solid waste silicon-aluminum-based ceramic membrane.
[0020] Furthermore, in the process of preparing the solid waste silicon-aluminum-based ceramic membrane, the raw material is crushed into a raw material that is ground and then passed through a 100-mesh molecular sieve.
[0021] Furthermore, in the preparation process of the solid waste silicon-aluminum-based ceramic membrane, the ball milling is performed at a rotation speed of 330-380 r / min for 18-24 hours.
[0022] Furthermore, during the preparation of the solid waste silicon-aluminum-based ceramic membrane, the pressing is performed at 5-8 MPa.
[0023] Furthermore, in the preparation process of solid waste silicon-aluminum-based ceramic membrane, the calcination is carried out in an air atmosphere and is divided into three stages. The first stage: heating to 200°C at a heating rate of 5°C / min and keeping warm for 40 minutes; the second stage: heating to 600°C at a heating rate of 2°C / min and keeping warm for 60 minutes; the third stage: heating to 950-1100°C at a heating rate of 3°C / min and keeping warm for 150 minutes.
[0024] Furthermore, in the preparation process of the solid waste silicon-aluminum-based ceramic membrane, the raw materials are crushed and then mixed and ball-milled, and the steps of drying, grinding and screening are also included. The drying is drying at 60-80°C for 12-14 hours, and the screening is through a 100-mesh sieve.
[0025] Furthermore, in the preparation process of the solid waste silicon-aluminum-based ceramic membrane, a cooling step is also included after the calcination, and the cooling step is to reduce the temperature to 500°C at a cooling rate of 4°C / min and then naturally cool to room temperature.
[0026] Furthermore, the preparation method of the α-Fe2O3 sol comprises the following steps:
[0027] Aluminum isopropoxide is ground into powder, water is added, refluxed and stirred, then ferric nitrate is added, the temperature is increased, and nitric acid solution is added and refluxed and stirred continuously to obtain the α-Fe2O3 sol.
[0028] Furthermore, during the preparation of the α-Fe2O3 sol, the molar ratio of aluminum isopropoxide to water is 1:100, the mass ratio of aluminum isopropoxide to ferric nitrate is 5:1, and the molar ratio of aluminum isopropoxide to nitric acid solution is 25:6.
[0029] Furthermore, during the preparation of the α-Fe2O3 sol, the temperature of the water is 84°C.
[0030] Furthermore, during the preparation of the α-Fe2O3 sol, water was added and the mixture was refluxed and stirred for 120 minutes, then ferric nitrate was added and the temperature was raised to 90°C, and nitric acid solution was added after 30 minutes, and refluxed and stirred at 90°C for 24 hours.
[0031] The third technical solution of the present invention:
[0032] The solid waste silicon-aluminum-based α-iron oxide ceramic membrane is used in treating oil-containing emulsion wastewater.
[0033] Compared with the prior art, the present invention has the following advantages and technical effects:
[0034] (1) The oil in the oil-water emulsion mainly exists in the form of tiny oil droplets. When passing through the surface of the ceramic membrane of the present invention, most of the oil droplets with a particle size larger than the pore size of the ceramic membrane surface will be blocked and adsorbed on one side of the ceramic membrane, and water molecules will penetrate from the oil-water side to the other side under the osmotic pressure. The α-iron oxide loaded on the ceramic membrane of the present invention has better hydrophilicity and oleophobicity on the premise of blocking the pore size of the ceramic membrane surface, making it easier for water molecules to pass through the ceramic membrane, thereby making it more difficult for oil droplets to adhere to the surface of the ceramic membrane.
[0035] (2) The present invention proposes a ceramic membrane that uses gold mine tailings and electroplating sludge as main raw materials and is sintered at low temperature, thereby realizing the recycling of solid waste resources, reducing production costs and saving energy consumption. Furthermore, the hydrophilic α-Fe2O3 is loaded on the ceramic membrane substrate to improve the oil rejection rate of the ceramic membrane. The present invention adopts a simple preparation method of dry pressing and low-temperature sintering, and realizes efficient treatment of high-concentration (2000ppm) oil-containing emulsion wastewater at a relatively low sintering temperature (950-1100°C). BRIEF DESCRIPTION OF THE DRAWINGS
[0036] The accompanying drawings constituting a part of the present invention are used to provide a further understanding of the present invention. The exemplary embodiments of the present invention and their descriptions are used to explain the present invention and do not constitute an improper limitation of the present invention. In the accompanying drawings:
[0037] Figure 1 This is a surface SEM image of the solid waste silicon-aluminum-based ceramic membrane prepared in step (1) of Example 1;
[0038] Figure 2 This is a surface SEM image of the solid waste silicon-aluminum-based α-Fe2O3 ceramic membrane prepared in Example 1;
[0039] Figure 3 These are pictures of the solid waste silicon-aluminum-based α-Fe2O3 ceramic membrane prepared in Example 1 before and after filtration of an oil-in-water emulsion, with the left side showing before filtration and the right side showing after filtration.
[0040] Figure 4 Graph showing the oil-water separation efficiency of the solid waste silicon-aluminum-based ceramic membranes prepared in Examples 1-3 and Comparative Examples 1-2. DETAILED DESCRIPTION
[0041] Various exemplary embodiments of the present invention will now be described in detail. This detailed description should not be considered as limiting the present invention, but should be understood as a more detailed description of certain aspects, features, and embodiments of the present invention.
[0042] It should be understood that the terms described in the present invention are only for describing special embodiments and are not intended to limit the present invention. In addition, for the numerical range in the present invention, it should be understood that each intermediate value between the upper and lower limits of the scope is also specifically disclosed. Each smaller range between the intermediate value in any stated value or stated range and any other stated value or intermediate value in the described range is also included in the present invention. The upper and lower limits of these smaller ranges can be independently included or excluded in the scope.
[0043] Unless otherwise indicated, all technical and scientific terms used herein have the same meanings as those generally understood by those skilled in the art. Although the present invention describes only preferred methods and materials, any methods and materials similar or equivalent to those described herein may also be used in the implementation or testing of the present invention. All documents mentioned in this specification are incorporated by reference to disclose and describe the methods and / or materials associated with the documents. In the event of a conflict with any incorporated document, the content of this specification shall prevail.
[0044] It will be apparent to those skilled in the art that various modifications and variations may be made to the specific embodiments of the present invention description without departing from the scope or spirit of the present invention. Other embodiments derived from the present invention description will be apparent to those skilled in the art. The present invention description and examples are exemplary only.
[0045] The words “include,” “including,” “have,” “contain,” etc. used in this document are open-ended terms, meaning including but not limited to.
[0046] The embodiment of the present invention provides a solid waste silicon-aluminum-based α-iron oxide ceramic membrane (solid waste silicon-aluminum-based α-Fe2O3 ceramic membrane), comprising a solid waste silicon-aluminum-based ceramic membrane and an α-Fe2O3 sol coated on one side of the solid waste silicon-aluminum-based ceramic membrane;
[0047] The coating amount of the α-Fe2O3 sol on the surface of the solid waste silicon-aluminum-based ceramic membrane is 0.1-0.3 mL·cm -2 As an example, the coating amount in the embodiment of the present invention is 0.15 mL·cm -2 ;
[0048] The solid waste silicon-aluminum-based ceramic membrane raw materials include gold mine tailings, electroplating sludge, bran, aluminum oxide and silicon dioxide.
[0049] In a preferred embodiment of the present invention, the mass ratio of the gold mine tailings and the electroplating sludge is (0-3): (3-0), wherein the amount of the gold mine tailings and the electroplating sludge is not 0; the bran accounts for 2% of the total mass of the solid waste silicon-aluminum-based ceramic membrane raw materials; the aluminum oxide accounts for 9% of the total mass of the solid waste silicon-aluminum-based ceramic membrane raw materials; the silicon dioxide accounts for 4% of the total mass of the solid waste silicon-aluminum-based ceramic membrane raw materials; as an example, the mass ratio of the gold mine tailings and the electroplating sludge in the embodiment of the present invention is 1:1, 1:2 and 2:1.
[0050] The embodiment of the present invention also proposes a method for preparing the solid waste silicon-aluminum-based α-iron oxide ceramic membrane, wherein α-Fe2O3 sol is coated on one surface of the solid waste silicon-aluminum-based ceramic membrane, and then dried and calcined to obtain the solid waste silicon-aluminum-based α-iron oxide ceramic membrane.
[0051] In a preferred embodiment of the present invention, the drying temperature is 60-80° C. and the drying time is 6-12 hours; as an example, the drying temperature in the embodiment of the present invention is 80° C. and the drying time is 8 hours.
[0052] In a preferred embodiment of the present invention, the calcination is carried out by heating the material to 500° C. at a heating rate of 5° C. / min in an air atmosphere, keeping the temperature for 120 minutes, and then cooling the material to room temperature.
[0053] In a preferred embodiment of the present invention, the method for preparing the solid waste silicon-aluminum-based ceramic membrane comprises the following steps:
[0054] The gold mine tailings, electroplating sludge, bran, aluminum oxide and silicon dioxide raw materials are crushed and then mixed and ball-milled to obtain ceramic membrane powder, and the ceramic membrane powder is pressed and calcined to obtain the solid waste silicon-aluminum-based ceramic membrane;
[0055] The raw material crushing is grinding the raw material and then passing it through a 100 mesh molecular sieve; the ball milling is performed at a speed of 330-380 rpm for 12-18 hours; the pressing is performed at 5-8 MPa; the calcination is performed in an air atmosphere and is divided into three stages: the first stage: heating to 200°C at a heating rate of 5°C / min and keeping warm for 40 minutes; the second stage: heating to 600°C at a heating rate of 2°C / min and keeping warm for 60 minutes; the third stage: heating to 950-1 100°C, keep warm for 150 minutes; as an example, the ball milling in the embodiment of the present invention is ball milling at a speed of 387 rpm for 18 hours; the pressing is pressing at 6MPa; the calcination is carried out in an air atmosphere and is divided into three stages, the first stage: heating to 200°C at a heating rate of 5°C / min, and keeping warm for 40 minutes; the second stage: heating to 600°C at a heating rate of 2°C / min, and keeping warm for 60 minutes; the third stage: heating to 1050°C at a heating rate of 3°C / min, and keeping warm for 150 minutes.
[0056] In a preferred embodiment of the present invention, in the preparation process of solid waste silicon-aluminum-based ceramic membrane, the raw materials are crushed and then mixed and ball-milled, which also includes the steps of drying, grinding and screening. The drying is drying at 60-80°C for 12-14 hours, and the screening is passing through a 100-mesh sieve; as an example, the drying in the embodiment of the present invention is drying at 80°C for 12 hours.
[0057] In a preferred embodiment of the present invention, during the preparation of the solid waste silicon-aluminum-based ceramic membrane, a cooling step is also included after the calcination, and the cooling step is to cool the temperature to 500°C at a cooling rate of 4°C / min and then naturally cool to room temperature.
[0058] In a preferred embodiment of the present invention, the method for preparing the α-Fe2O3 sol comprises the following steps:
[0059] Aluminum isopropoxide is ground into powder, water is added and refluxed with stirring, then ferric nitrate is added and the temperature is raised, and nitric acid solution is added and the reflux is continued with stirring to obtain the α-Fe2O3 sol; wherein, further, in the preparation process of the α-Fe2O3 sol, the molar ratio of the aluminum isopropoxide to water is 1:100, the mass ratio of the aluminum isopropoxide to ferric nitrate is 5:1, and the molar ratio of the aluminum isopropoxide to nitric acid solution is 25:6; the temperature of the water is 84°C; water is added and refluxed with stirring for 120 minutes, then ferric nitrate is added and the temperature is raised to 90°C, nitric acid solution is added after 30 minutes, and reflux and stirring are continued at 90°C for 24 hours.
[0060] The room temperature in the embodiments of the present invention refers to "25±2°C".
[0061] All raw materials used in the examples of the present invention are commercially available.
[0062] In the gold mine tailings used in the embodiment of the present invention, the main minerals contained are quartz 44.6%, gypsum 13.2%, orthoclase 16% and pyrite 26.2% by mass percentage.
[0063] In the electroplating sludge used in the embodiment of the present invention, the main minerals contained are 68.3% quartz and 31.7% albite, calculated by mass percentage.
[0064] The technical solution of the present invention is further illustrated by the following embodiments.
[0065] Example 1
[0066] (1) Preparation of Si-Al-based Ceramic Membranes from Solid Waste
[0067] The gold mine tailings and electroplating sludge are dried in a drying oven to constant weight and dehydrated, then taken out, crushed and ground, and sieved through a 100-mesh stainless steel sieve for later use; the bran is ground and crushed, and sieved through a 100-mesh stainless steel sieve for later use; the aluminum oxide and silicon dioxide are ground and crushed, and sieved through a 100-mesh stainless steel sieve for later use;
[0068] Weigh the raw materials according to the following mass ratio: the mass ratio of gold mine tailings and electroplating sludge is 1:1; bran accounts for 2% of the total mass of solid waste silicon-aluminum-based ceramic membrane raw materials; aluminum oxide accounts for 9% of the total mass of solid waste silicon-aluminum-based ceramic membrane raw materials; silicon dioxide accounts for 4% of the total mass of solid waste silicon-aluminum-based ceramic membrane raw materials;
[0069] The crushed gold mine tailings, electroplating sludge, bran, aluminum oxide and silicon dioxide were mixed, and evenly mixed and ball-milled in a grinding body with ethanol as the medium for 18 hours. The speed of the planetary ball mill was set to 360 rpm. After being evenly mixed, the slurry was taken out and washed and collected with anhydrous ethanol. It was then dried in an oven at 80°C for 12 hours and passed through a 100-mesh sieve to obtain a ceramic membrane powder.
[0070] The obtained ceramic membrane powder is placed in a mold (Φ=40mm) and pressed into a ceramic membrane embryo with a diameter of 40mm and a thickness of 1.5-1.6mm under 6MPa conditions. The ceramic membrane embryo is then calcined in an air atmosphere. The calcination is divided into three stages: the first stage: heating to 200°C at a heating rate of 5°C / min and keeping warm for 40 minutes; the second stage: heating to 600°C at a heating rate of 2°C / min and keeping warm for 60 minutes; the third stage: heating to 1050°C at a heating rate of 3°C / min and keeping warm for 150 minutes; after the calcination, the temperature is reduced to 500°C at a cooling rate of 4°C / min and then naturally cooled to room temperature to obtain a solid waste silicon-aluminum-based ceramic membrane.
[0071] (2) Preparation of α-Fe2O3 sol
[0072] 5.1 g of aluminum isopropoxide was ground into powder using an agate mortar and pestle, and added into a round-bottom flask filled with 84° C. hot water, the molar ratio of aluminum isopropoxide to water being 1:100. The mixture was refluxed and stirred at 84° C. for 120 minutes, and then 1.02 g of ferric nitrate was added and the temperature was raised to 90° C. After 30 minutes, 3.34 mL of nitric acid solution (concentration of 1.8 mol / L) was added to complete the peptization step. The mixture was refluxed and stirred at 90° C. for 24 hours to complete aging and obtain α-Fe2O3 sol.
[0073] (3) Preparation of Si-Al-based α-Fe2O3 Ceramic Membranes from Solid Waste
[0074] The solid waste silicon-aluminum-based ceramic membrane prepared in step (1) was washed clean in ultrapure water and dried in a blast drying oven. Then, the α-Fe2O3 sol prepared in step (2) was evenly coated on one side of the dried solid waste silicon-aluminum-based ceramic membrane. The coating amount was 0.15 mL·cm -2 , and then dried in a drying oven at 80°C for 8 hours. After drying, the temperature was increased to 500°C at a heating rate of 5°C / min in an air atmosphere, kept warm for 120 minutes, and then cooled to room temperature to obtain a solid waste silicon-aluminum-based α-Fe2O3 ceramic membrane. The solid waste silicon-aluminum-based α-Fe2O3 ceramic membrane prepared in this embodiment is recorded as CM-C.
[0075] Example 2
[0076] The same as Example 1, the only difference is that in step (1), the mass ratio of gold mine tailings to electroplating sludge is 1:2. The solid waste silicon-aluminum-based α-Fe2O3 ceramic membrane prepared in this example is recorded as CM-B.
[0077] Example 3
[0078] The same as Example 1, the only difference is that in step (1), the mass ratio of gold mine tailings to electroplating sludge is 2:1. The solid waste silicon-aluminum-based α-Fe2O3 ceramic membrane prepared in this example is recorded as CM-D.
[0079] Comparative Example 1
[0080] The same as Example 1, except that the preparation of the solid waste silicon-aluminum-based ceramic membrane in step (1) is different and does not contain electroplating sludge, specifically:
[0081] The gold tailings are dried in a drying oven to constant weight and dehydrated, then taken out, crushed, ground, and sieved through a 100-mesh stainless steel sieve for later use; the bran is ground, crushed, and sieved through a 100-mesh stainless steel sieve for later use; the aluminum oxide and silicon dioxide raw materials are ground, crushed, and sieved through a 100-mesh stainless steel sieve for later use;
[0082] Weigh the raw materials according to the following mass ratio: the mass ratio of gold mine tailings and electroplating sludge is 3:0; bran accounts for 2% of the total mass of solid waste silicon-aluminum-based ceramic membrane raw materials; aluminum oxide accounts for 9% of the total mass of solid waste silicon-aluminum-based ceramic membrane raw materials; silicon dioxide accounts for 4% of the total mass of solid waste silicon-aluminum-based ceramic membrane raw materials;
[0083] The crushed gold ore tailings, bran, aluminum oxide and silicon dioxide raw materials were mixed, and evenly mixed and ball-milled in a grinding body with ethanol as the medium for 18 hours. The speed of the planetary ball mill was set to 387r / min. After uniform mixing, the slurry after ball milling was taken out and washed and collected with anhydrous ethanol, and then dried in an oven at 80°C for 12 hours, and passed through a 100-mesh sieve to obtain a ceramic membrane powder;
[0084] The obtained ceramic membrane powder is placed in a mold (Φ=40mm) and pressed into a ceramic membrane embryo with a diameter of 40mm and a thickness of 1.5-1.6mm under the condition of 6MPa. The ceramic membrane embryo is then calcined in an air atmosphere. The calcination is divided into three stages: the first stage: heating to 200°C at a heating rate of 5°C / min and keeping warm for 40 minutes; the second stage: heating to 600°C at a heating rate of 2°C / min and keeping warm for 60 minutes; the third stage: heating to 1050°C at a heating rate of 3°C / min and keeping warm for 150 minutes; after the calcination, the temperature is reduced to 500°C at a cooling rate of 4°C / min and then naturally cooled to room temperature to obtain a solid waste silicon-aluminum-based ceramic membrane. The solid waste silicon-aluminum-based ceramic membrane prepared in this comparative example is recorded as CM-E.
[0085] Comparative Example 2
[0086] The same as Example 1, except that the preparation of the solid waste silicon-aluminum-based ceramic membrane in step (1) is different and does not contain gold mine tailings, specifically:
[0087] The electroplating sludge is dried in a drying oven to constant weight and dehydrated, then taken out, crushed, and sieved through a 100-mesh stainless steel sieve for later use; the bran is ground, crushed, and sieved through a 100-mesh stainless steel sieve for later use; the aluminum oxide and silicon dioxide raw materials are ground, crushed, and sieved through a 100-mesh stainless steel sieve for later use;
[0088] Weigh the raw materials according to the following mass ratio: the mass ratio of gold mine tailings and electroplating sludge is 0:3; bran accounts for 2% of the total mass of solid waste silicon-aluminum-based ceramic membrane raw materials; aluminum oxide accounts for 9% of the total mass of solid waste silicon-aluminum-based ceramic membrane raw materials; silicon dioxide accounts for 4% of the total mass of solid waste silicon-aluminum-based ceramic membrane raw materials;
[0089] The crushed electroplating sludge, bran, aluminum oxide and silicon dioxide raw materials were mixed, and evenly mixed and ball-milled in a grinding body with ethanol as the medium for 18 hours. The speed of the planetary ball mill was set to 387r / min. After uniform mixing, the slurry after ball milling was taken out and washed and collected with anhydrous ethanol, and then dried in an oven at 80°C for 12 hours, and passed through a 100-mesh sieve to obtain a ceramic membrane powder;
[0090] The obtained ceramic membrane powder is placed in a mold (Φ=40mm), and pressed into a ceramic membrane embryo with a diameter of 40mm and a thickness of 1.5-1.6mm under the condition of 6MPa. The ceramic membrane embryo is then calcined in an air atmosphere, and the calcination is divided into three stages: the first stage: heating to 200°C at a heating rate of 5°C / min, and keeping warm for 40 minutes; the second stage: heating to 600°C at a heating rate of 2°C / min, and keeping warm for 60 minutes; the third stage: heating to 1050°C at a heating rate of 3°C / min, and keeping warm for 150 minutes; after the calcination, the temperature is reduced to 500°C at a cooling rate of 4°C / min, and then naturally cooled to room temperature to obtain a solid waste silicon-aluminum-based ceramic membrane. The solid waste silicon-aluminum-based ceramic membrane prepared in this comparative example is recorded as CM-A.
[0091] Performance Testing
[0092] The surface SEM image of the solid waste silicon-aluminum-based ceramic membrane prepared in step (1) of Example 1 is shown in Figure 1 The surface SEM image of the solid waste silicon-aluminum-based α-Fe2O3 ceramic membrane prepared in Example 1 is shown in Figure 2 ,from Figure 1 It can be seen that the surface of the solid waste silicon-aluminum-based ceramic membrane is defect-free and presents a porous structure, with obvious sintering necks between the particles. Figure 2 It can be seen that after coating with α-Fe2O3 sol, the macropores of the solid waste silicon-aluminum-based ceramic membrane are blocked and the roughness of the membrane surface is increased.
[0093] The fine ceramic three-point bending method was used to test the bending strength of the solid waste silicon-aluminum-based α-Fe2O3 ceramic membrane prepared in Example 1. The results showed that the strength was ~26.2MPa.
[0094] The solid waste silicon-aluminum-based α-Fe2O3 ceramic membrane prepared in Example 1 was subjected to dead-end filtration under an osmotic pressure of 1 bar. Pure water permeated from one side of the ceramic membrane to the other side under the osmotic pressure. The volume of the permeated pure water obtained in the 10-minute permeation test was converted to obtain the pure water flux of the ceramic membrane. The results showed that the pure water permeability of the solid waste silicon-aluminum-based α-Fe2O3 ceramic membrane prepared in Example 1 was about 420 L·m -1 ·Hour -1 bar -1 At 0.5 bar and 0.5 m / s, the retention rate of 2000 ppm oil-in-water emulsion reaches 98.2%.
[0095] The solid waste silicon-aluminum-based α-Fe2O3 ceramic membrane prepared in Example 1 was tested for water-in-oil emulsion permeability. The test method was the same as the pure water permeability test process mentioned above. During the experiment, the emulsion first passed through the side coated with α-Fe2O3. The pictures before and after the solid waste silicon-aluminum-based α-Fe2O3 ceramic membrane prepared in Example 1 filtered 2000ppm of water-in-oil emulsion are shown in Figure 3 The left side is before filtration, and the right side is after filtration. It can be seen that after filtration by the solid waste silicon-aluminum-based α-Fe2O3 ceramic membrane, the permeate is clear and transparent, and almost no oil droplets can be observed, proving that the solid waste silicon-aluminum-based α-Fe2O3 ceramic membrane has excellent oil-water separation performance.
[0096] The oil-water separation efficiency of the solid waste silicon-aluminum-based ceramic membrane prepared in Examples 1-3 and Comparative Examples 1-2 is shown in FIG. Figure 4 It can be seen that when the ratio of gold tailings to electroplating sludge is 1:1, the prepared solid waste silicon-aluminum-based ceramic membrane provides a larger separation flux while retaining a higher separation efficiency, which is the preferred solid waste silicon-aluminum-based ceramic membrane matrix prepared, and α-Fe2O3 is loaded on this basis.
[0097] The above are only preferred specific embodiments of the present invention, but the protection scope of the present invention is not limited thereto. Any changes or substitutions that can be easily thought of by a person skilled in the art within the technical scope disclosed by the present invention should be included in the protection scope of the present invention. Therefore, the protection scope of the present invention should be based on the protection scope of the claims.
Claims
1. A solid waste silicon-aluminum-based α-iron oxide ceramic membrane, characterized in that: It comprises a solid waste silicon-aluminum-based ceramic membrane and an α-Fe2O3 sol coated on one side of the solid waste silicon-aluminum-based ceramic membrane; The coating amount of the α-Fe2O3 sol on the surface of the solid waste silicon-aluminum-based ceramic membrane is 0.1-0.3 mL·cm -2 ; The raw materials of the solid waste silicon-aluminum-based ceramic membrane include gold mine tailings, electroplating sludge, bran, aluminum oxide and silicon dioxide.
2. The solid waste silicon-aluminum-based α-iron oxide ceramic membrane according to claim 1, characterized in that: The mass ratio of the gold mine tailings to the electroplating sludge is (0-3): (3-0), wherein the dosage of the gold mine tailings and the electroplating sludge is not 0; The bran accounts for 2% of the total mass of the solid waste silicon-aluminum-based ceramic membrane raw materials; The aluminum oxide accounts for 9% of the total mass of the solid waste silicon-aluminum-based ceramic membrane raw materials; The silicon dioxide accounts for 4% of the total mass of the solid waste silicon-aluminum-based ceramic membrane raw materials.
3. A method for preparing a solid waste silicon-aluminum-based α-iron oxide ceramic membrane according to any one of claims 1 to 2, characterized in that: The α-Fe2O3 sol is coated on one side of the solid waste silicon-aluminum-based ceramic membrane, and then dried and calcined to obtain the solid waste silicon-aluminum-based α-iron oxide ceramic membrane.
4. The method for preparing the solid waste silicon-aluminum-based α-iron oxide ceramic membrane according to claim 3, characterized in that: The drying temperature is 60-80°C and the drying time is 6-12 hours; and / or The calcination was carried out by heating the temperature to 500° C. at a heating rate of 5° C. / min in an air atmosphere, maintaining the temperature for 120 minutes, and then cooling to room temperature.
5. The method for preparing the solid waste silicon-aluminum-based α-iron oxide ceramic membrane according to claim 3, characterized in that: The method for preparing the solid waste silicon-aluminum-based ceramic membrane comprises the following steps: The solid waste silicon-aluminum-based ceramic membrane raw material is crushed and then mixed and ball-milled to obtain ceramic membrane powder, and the ceramic membrane powder is pressed and calcined to obtain the solid waste silicon-aluminum-based ceramic membrane.
6. The method for preparing the solid waste silicon-aluminum-based α-iron oxide ceramic membrane according to claim 5, characterized in that: The solid waste silicon-aluminum-based ceramic membrane raw material is crushed into raw materials, ground and then passed through a 100-mesh molecular sieve; and / or The ball milling is performed at a rotation speed of 330-380 rpm for 18-24 hours; and / or The pressing is performed at 5-8 MPa; and / or The calcination is carried out in an air atmosphere, comprising: heating to 200° C. at a heating rate of 5° C. / min, and keeping the temperature for 40 minutes; Then, the temperature was increased to 600°C at a heating rate of 2°C / min and kept at that temperature for 60 minutes; then, the temperature was increased to 950-1100°C at a heating rate of 3°C / min and kept at that temperature for 150 minutes.
7. The method for preparing the solid waste silicon-aluminum-based α-iron oxide ceramic membrane according to claim 3, characterized in that: The preparation method of the α-Fe2O3 sol comprises the following steps: Aluminum isopropoxide is ground into powder, water is added, refluxed and stirred, then ferric nitrate is added, the temperature is increased, and nitric acid solution is added and refluxed and stirred continuously to obtain the α-Fe2O3 sol.
8. The method for preparing the solid waste silicon-aluminum-based α-iron oxide ceramic membrane according to claim 7, characterized in that: The molar ratio of the aluminum isopropoxide to water is 1:100, the mass ratio of the aluminum isopropoxide to ferric nitrate is 5:1, and the molar ratio of the aluminum isopropoxide to nitric acid solution is 25:
6.
9. The method for preparing the solid waste silicon-aluminum-based α-iron oxide ceramic membrane according to claim 7, characterized in that: The temperature of the water is 84°C; Water was added and the mixture was refluxed and stirred for 120 minutes. Then, ferric nitrate was added and the temperature was raised to 90°C. After 30 minutes, nitric acid solution was added and refluxed and stirred at 90°C for 24 hours.
10. Use of the solid waste silicon-aluminum-based α-iron oxide ceramic membrane according to any one of claims 1 to 2 in treating oil-containing emulsion wastewater.
Citation Information
Patent Citations
Alumina ceramic membranes
CA2819791A1
Micro-filtration ceramic membrane using waste materials as raw materials and preparation method thereof
CN108546149A
Solid waste-based ceramic catalytic membrane and preparation method and application thereof
CN111410547A
Anti-pollution ceramic membrane as well as preparation method and application thereof
CN113926321A
Granite-based gold ore tailing-doped ceramic filter membrane as well as preparation process and application of granite-based gold ore tailing-doped ceramic filter membrane
CN114213103A